Eros e Ágape - Minne: o cúmulo do amor na luz fluente da deidade - das flieBende Licht der Gottheit de Mechthild de Magdeburg - Amaral, Maria José Caldeira do (2008)
The main objective of this research is the prospect of a deeper study on mysticism as a possibility for enlarging the knowledge in the symbolic and fundamental field of the Sciences of Religion. Our interest in researching the medieval records of Mechthild of Magdeburg, the flieBende Das Licht der Gottheit - object of this essay - is based on the feasibility of contributing to the debate on the human condition, emphasizing the inherent knowledge of the soul that loves God, disregarding her own self as consisted literally in the language of the text under study. Our hypothesis is that the movement extended over the established senses in concepts belonging to the religious context of western Christianity with reference to love, eros and agape, - as a key to reading -, sustains a possible understanding of love itself, from the development of a hermeneutic of the mystical language in focus. The loyalty to Mechthild of Magdeburg s records, written in vernacular language, the speculation of authors before and contemporary to her, and information of the religious medieval female authors, of the so called Frauenmyistic (female mysticism), formalized the development of our speculation around the mystique of love unfolded in the infusion of love as a deity. The Love of God, substantiated in the essence of the condition of the soul in distress by the inexorable search for that love, unfolds in the apex of love - concept formalized in the final construction of the research - as the best way of setting the dynamics between eros and agape available in the language of the flieBende Licht der Gottheit